2006
DOI: 10.1080/03235400400007533
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and diversity ofFusariumspp. colonizing roots of Egyptian cottons

Abstract: Fusarium species are known to play a role in several diseases of cotton including the seedling disease complex, wilt, and boll rot. Therefore, a mycoflora study was conducted in 1998 in order to identify Fusarium species found in association with cotton roots. A total of 109 samples of cotton seedlings infected with post-emergence damping-off or rotted roots of adult plants were obtained from different cottongrowing areas in Egypt. Forty-six isolates were recovered and were identified

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…are isolated from cotton seedlings (1,8,39,59). Sacc, have been demonstrated (1,8,9,36,59). indicated that most species are of minor significance in the etiology of cotton seedling disease (17,24,36).…”
mentioning
confidence: 99%
“…are isolated from cotton seedlings (1,8,39,59). Sacc, have been demonstrated (1,8,9,36,59). indicated that most species are of minor significance in the etiology of cotton seedling disease (17,24,36).…”
mentioning
confidence: 99%
“…In Egypt, F. oxysporum was frequently isolated from cotton seedlings infected with damping-off (Aly et al, 1996 andEl-Samawaty, 1999). Also, F. solani was pathogenic for eighty-three percentage of collected isolates (Abd-Elsalam et al, 2006). In another study Johnson et.…”
Section: Introductionmentioning
confidence: 93%
“…often are the most frequently isolated fungi from cotton seedlings (34,26,47,22,56). Isolates of several species have been demonstrated to be pathogenic (66,22,23,56,1). Symptoms caused by Fusarium spp.…”
Section: Causal Agentsmentioning
confidence: 99%